Understanding Taoism - "Moore,Jennifer oldstone" (London, 2003)
A vivid portrait of a profound tradition - from the Tao Te Ching to the ethics of "going with the flow" This concise, illustrated introduction is an accessible introduction to the nine key themes of Taoism - including the life of its founding sage Laozi and his teachings, the influential sacred writings of the Tao Te Jing and Zhuangzi, the concept of wu wei (non interference), the cultivation of simplicity and detachment, the attainment of harmony and the quest for immortality. Jennifer Oldstone-Moore provides a unique distillation of this highly distinctive tradition, from its origins in ancient China to its place in society today, this book includes special documentary sections presenting summaries of key texts.
Keywords: Religion